(untitled) (Orinoquia, 2021)
The relationships that human beings have built with microorganisms, plants and animals have enabled our modern society to develop technologically. Human populations in ancient times fed themselves by hunting, fishing, gathering plants and/or their products. Subsequently, organisms began to be domesticated for food crops in the early Holocene period ( 11,700 years ago); however, it was not until the beginning of the Neolithic era ( 10-11 thousand years ago) that rudimentary technology was developed for such purpose. These conditions enabled the emergence of agriculture-based societies in Eurasia, North Africa and Central and South America. The beginnings of aquaculture date back around 4,000 years ago in China. Since their origins, such ancient activities have motivated human beings to create technological systems for improving crop production rates and meeting food demand. It is thus no coincidence that many modern technological and scientific advances are linked to applications for agricultural and aquaculture production. A considerable increase in the human population (9.9 billion people) is expected by 2050 according to various international organisations; this will be accompanied by the consequent increased demand for food and environmental resources. Some strategies have even begun to be developed to avoid food shortages during the next three decades; increasing crop yields and improving global food production systems are priorities imposed by such scenario. Better understanding of genes and genomes’ functional structure, along with organisms’ physiological responses to dietary and/or environmental changes is required for achieving such goals. Humanity’s access to a large amount of information has increased substantially during recent decades; biological sciences have not been the exception. A holistic approach called Systems Biology currently uses mathematical models to represent the interactions of elements influencing biological processes. Emerging omic technologies/sciences and data analysis techniques can be used to understand molecular phenomena; omics-based analysis enables quantifying and characterising the groups of molecules involved in the structure or biological function of a cell, tissue or organism regarding a particular time and set conditions. Genomics, proteomics and metabolomics are omic sciences that study genes, proteins and metabolites’ molecular relationships with a determined final phenotype. The three main omic sciences have engendered many offshoots; some of the most commonly used ones are transcriptomics which studies which genes are active or expressed and epigenomics which studies how DNA-related gene activity or expression is controlled. Both disciplines help to describe how the environment (medicines, diet, behaviour, interactions, radiation, climate, pollution) modulates the expression of certain genes. Microbiomics studies microorganism population changes in various environments (soil, water, air, food, animal bodies) when an external factor changes their quality or quantity (feeding, temperature, photoperiod, social interaction). The genomic sequences for some organisms and microorganisms cultivated around the world have been obtained in recent years; this information has been used to assess their molecular architecture, structure and complexity, as well as for describing certain of their unique genomic features. Molecular markers have been identified in some terrestrial and aquaculture organisms’ genetic lines, enabling specific genes to be connected with phenotypical characteristics regarding production performance and significant economic traits (better feed conversion rates, accelerated growth, reproductive efficiency, product quality, susceptibility to diseases).